Social Media Consumption in Klang Valley: Generation Z’s Desired Content on Instagram - Yue, Kee Chain; Lee, Chew Wee (Procedia of Social Sciences and Humanities, 2024)
Social media has become an integral part of Generation Z’s daily lives, with platforms like Instagram being particularly dominant in shaping their consumption habits and interaction patterns. This study investigates the social media consumption behavior of Generation Z in Klang Valley, focusing on their preferred content types and the underlying motivations for engaging with digital marketing content on Instagram. Employing the Uses and Gratifications Theory, this research seeks to understand how Generation Z interacts with content, what drives their engagement, and what types of content they are most likely to share or respond to.The findings suggest that entertainment is the primary motivator for Instagram use, although factors such as aesthetics, brand reputation, and discounts also significantly influence their engagement. However, the consumption of content does not always align with engagement patterns, indicating that passive consumption might be prevalent. The research also highlights the role of Instagram as a medium for entertainment and visual appeal, with Gen Z valuing content that is easy to engage with and visually stimulating. Brands targeting this demographic should focus on these factors to enhance interaction and engagement with their products.In conclusion, the study offers insights into how brands can adapt their strategies to align with Generation Z’s preferences by emphasizing entertainment value, visual quality, and ease of interaction. By tailoring marketing strategies to meet these needs, brands can enhance their online presence and engagement with the young, tech-savvy population of Generation Z in Klang Valley.